What Makes Teachers Stay in an Organization? The Case of a Private University in Northern Philippines - Ivan Clark R Cabasal; Paula Lorraine A Pua; Constantino A Soriano; Maria Jose C Talosig; Marie Jhoy Nica G Yadan; Gladys Tumbali; John Mosel Bitonio; Karen Joy Catacutan (Advanced Qualitative Research, 2025)
Teachers are fundamental to a university’s success, and their satisfaction and motivation are essential for institutional growth. This study explores the factors influencing teachers’ retention at the University of Saint Louis, Tuguegarao, aiming to uncover and analyze key elements behind their long-term commitment. Using a qualitative method and descriptive research design, structured interviews with university teachers provided insights into their reasons for staying. The study identified one central theme: Various Factors Affecting Teachers’ Decision to Stay, which includes two subthemes: Extrinsic Factors (e.g., salary, benefits, work environment, and organizational policies) and Intrinsic Factors (e.g., job satisfaction, sense of purpose, and opportunities for professional growth). These findings highlight areas for the university to strengthen its strategies for managing employees and fostering a supportive environment. By addressing both tangible and personal motivators, the organization can ensure its educators feel valued and inspired to contribute to its long-term success